Anomalies in Internal Conversion Coefficients for Hindered γ-Transitions - Kirishchuk, V.I.; Lashko, A.P.; Lashko, T.N. (Ukrainian Journal of Physics, 2021)
New data concerning the penetration effect in the М1 component of hindered rotational γ-transitions have been obtained. The effect is caused by different selection rules for γ-emission and intranuclear conversion matrix elements. The magnitude of penetration parameter for the М1-component of the 129-keV γ-transition in 191Ir nucleus is determined for the first time. The results obtained for similar transitions in 163Er, 165Er, and 177Hf nuclei are also reported. By comparing the experimental penetration matrix elements with those calculated from the Nilsson model, the following renormalization coefficients are found for the gyromagnetic ratios for the spin-multipole interaction in М1-conversion transitions: gs(M1)/gsfree(p) = 0.574 ± 0.023 and gs(M1)/gsfree(n)=0.59±0.07.